A Bibliometric Analysis of Studies Concerning Policy Issues in Covid-19 Pandemic - Nguyen, The Thang; Dinh-Hai Luong; Hong-Lien Nguyen; Thi-Phuong Thao Vu; Hoai-Thu Nguyen (International Journal of Social Learning (IJSL), 2022)
This research analysed the studies of policy on issues related to COVID-19. The results show the most productive countries, the most frequently cited sources, the most co-occurred topics of studies concerning policy issues since the epidemic was a breakout at the beginning. The data in this research were collected from the Scopus database with two search terms, "COVID-19" and "policy" of the social science domain, and published from the first day of 2020 to the search time (September 10, 2020). The final dataset consists of 384 valid documents analysed by descriptive statistics, and co-occurrence analysis was applied in R. Among 46 countries, the United States, the United Kingdom, Australia, China, India, and Italy are the leading countries that published these studies. Almost all the funded scholars focused on Europe, the Americas, and Asia. The main topics of the articles are "working in COVID-19 period", "community health and social support," "using ICT in teaching and learning," "human rights." Within funded studies, four interesting topics are "social well-being," "ICT infrastructure," "agricultural policy," and "born-digital." This study presents the current situation of how studies concerning policy issues have been issued to respond to the COVID-19 pandemic.